Evaluating the anti-neuropathic effects of the thymol-loaded nanofibrous scaffold in a rat model of spinal cord injury - Amirian, Roshanak; Mohammadi Pour, Pardis; Maleki, Hassan; Fakhri, Sajad; Asgary, Sedigheh; Farzaei, Mohammad Hossein; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundSpinal cord injury (SCI) is a debilitating condition characterized by partial or complete loss of motor and sensory function caused by mechanical trauma to the spinal cord. Novel therapeutic approaches are continuously explored to enhance spinal cord regeneration and functional recovery.PurposeIn this study, we investigated the efficacy of the poly(vinyl alcohol) and chitosan (PVA/CS) scaffold loaded with different thymol concentrations (5, 10, and 15 wt%) in a rat compression model for SCI treatment compare to other (e.g., thymol and scaffold) control groups.Results and discussionThe thymol-loaded scaffold exhibited a smooth surface and a three-dimensional nanofibrous structure with nanoscale diameter. The conducted analyses verified the successful incorporation of thymol into the scaffold and its high water absorption, porosity, and wettability attributes. Behavioral assessment of functional recovery showed improving sensory and locomotor impairment. Furthermore, histopathological examinations indicated the regenerative potential of the thymol-loaded nanofiber scaffold, by neuronal survival.ConclusionTherefore, these findings suggest that the thymol-loaded nanofibrous scaffolds have promising pharmacological activities for alleviating neuropathic pain and addressing complications induced by SCI.